Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: Nancy Bleile-Kratzer and ? Carrying American Civil Liberties Union banner; Counter protester sign "Equal Rights for Unborn Women"